A new method of depositing high figure-of-merit porous PZT pyroelectric thick film using [001]-oriented PZT nanorod by electrophoresis deposition - Peng, Qiang-Xiang; Luo, Wen-Bo; Meng, Jia; Fu, Wu-Yue; Qing, Xiao; Sun, Xiang-Yu; Shuai, Yao; Wu, Chuan-Gui; Zhang, Wang-Li (Journal of materials science. Materials in electronics, 2014)
The effects of hydrothermal synthesized [001]-oriented PZT nanorods on the pyroelectric properties of PZT thick film fabricated by electrophoresis deposition were studied in a range from 750 to 900 °C. It was revealed by scanning electron microscopy that the pores are mainly distributed in the film body but not at the electrode interface, which would improve the adhesion and electric contact between the thick film and electrode. The formation and distribution of the pores resulted from the PZT nanorods were schematically explained. It was found that the relative dielectric constant ( ε r ) of the PZT nanorod-doping film sintered at 800 °C was lowered by approximate 46.5 %. Accordingly, the calculated figures of merit for voltage responsivity (F V ) and detectivity (F D ) were improved by 125 and 114 %, respectively. These results demonstrated that a new way to deposit PZT porous thick film with low dielectric constant and high figures of merit was established.